Marketing model of sinarmas land through instagram platform - Nino Nopriandi Saleh; Lovia Evanne; Jefri Pranata (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
Digital marketing has now become the main source of income and marketing operation between many sectors and industries. Their focus revolved around content producing, that includes the property industry. The property industry operates their digital marketing through some social media accounts using Instagram, their background is diverse including the goal and pricing. When the author analysed the Instagram posts, a bold narration about property as future investment are displayed clearly; thus, with Krippendorff’s content analysis, Author could find more and illustrate it into the marketing model. The marketing model helps the reader to illustrate the business cycle with simplistic.